2022
DOI: 10.2174/1567201818666210609164704
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antibacterial Activity of Doxycycline and Rifampicin Combination Loaded in Nanoparticles against Intracellular Brucella abortus

Abstract: Background: Brucellosis is a zoonotic disease and prevalent in livestock animals. The bacteria reside inside the macrophage cells of host. The WHO endorsed the combination treatment therapy for brucellosis as compared to monotherapy to avoid relapse and resistance. Therefore, we developed nanoparticles incorporating doxycycline and rifampicin in combination. Objective: The aim of the study is to develop polymeric nanoparticles incorporating doxycycline as well as rifampicin and investigate the antibacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…DSC study demonstrated that FAV showed the presence of endotherms at 189.91 °C, implying crystallinity. The melting endotherms of favipiravir has not been observed in nanoparticles, indicating amorphous form [ 38 ]. Additionally, DSC study also suggested formation of nanoparticles with encapsulation of drug inside nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DSC study demonstrated that FAV showed the presence of endotherms at 189.91 °C, implying crystallinity. The melting endotherms of favipiravir has not been observed in nanoparticles, indicating amorphous form [ 38 ]. Additionally, DSC study also suggested formation of nanoparticles with encapsulation of drug inside nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics sharp and intense peak of favipiravir was obsereved by XRD. Whereas, the XRD diffractograms of nanoparticles showed less intensity of FAV suggesting amporphization of drug which is in coroborration with DSC studies [ 38 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%